Exploring the vegetation: Seed harvester ants climb and remove seeds from a giant cactus in a semiarid environment. (September 2018) - Luna, Pedro; Anjos, Diego; García-Chávez, Juan H.; Dáttilo, Wesley
Abstract: The red harvester ant ( Pogonomyrmex barbatus ) was observed in situ for the first time climbing and directly removing seeds from different individuals of the giant cactus Neobuxbaumia tetetzo in a Neotropical semiarid environment in central Mexico. Here, we explain how this harvester ant species, by overcoming a vertical barrier (reaching up 3.46 m), has amplified the two-dimensional spatial dimensions in which its worker ants may forage. We discuss the ecological traits that could drive this unusual behavior and its possible implications for the cactus.